Normative Evaluation of Tax Policies : From Households to Individuals - Olivier Bargain (Institute for the Study of Labor (IZA), 2004)
In this paper, we analyze the impact of a tax policy change on social welfare by using jointly a collective model of household labor supply and a microsimulation program of the French taxbenefit system. The collective approach allows studying the intrahousehold distribution so that for the first time, social welfare can be characterized using individual utilities rather than an ambiguous concept of household welfare. This way, the planner?s preferences address not only inter-household inequalities but also intra-household inequalities often neglected in the literature. The other contribution of the paper derives from a larger interpretation of labor supply behaviors which represent more than the simple work duration and incorporate unobserved dimensions related to effort or intensity at work. We simulate an extended version of the British Working Family Tax Credit on married couples in France. Two types of conclusions emerge. First, the reform is not desirable for low values (utilitarian) or high values (rawlsian) of the social inequality aversion but rather for an intermediary range. In effect, on the efficiency side, the reform induces strong disincentive effects on the participation of second-earners while on the equity side, it does not specifically target the poorest households. Second, we show that the choice of unit – household or individual – strongly condition the results of the normative analysis when departing in a reasonable way from the assumption of equal sharing within the household.
Keywords: C71; H31; D31; J22; H21; D63; D13; 330; collective model; intrahousehold distribution; social welfare; household labor supply; microsimulation; tax reform; Steuersystem; Sozialtransfer; Haushaltsökonomik; Steuerreform; Wohlfahrtseffekt; Frankreich